2007
DOI: 10.1111/j.1365-277x.2007.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic, as well as conventional yogurt, can enhance the stimulated production of proinflammatory cytokines

Abstract: Both conventional and probiotic yogurt enhanced the stimulated production of pro-inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 40 publications
(42 reference statements)
3
56
0
2
Order By: Relevance
“…These data are in agreement with previous findings reported for the RAW 264.7 macrophage cell line (Tejada-Simon and Pestka, 1999). Moreover, nutritional studies strengthened these findings showing production of TNF-␣ in individuals following consumption of conventional or probiotic yogurt containing Lactobacillus bulgaricus and Streptococcus thermophilus (Meyer et al, 2007). Interestingly, all tested strains were found effective in influencing iDCs in a mixed lymphocyte reaction with allogeneic T cells, thus suggesting that the phenotype of the inducible immune response is independent of the APC function.…”
Section: Discussionsupporting
confidence: 93%
“…These data are in agreement with previous findings reported for the RAW 264.7 macrophage cell line (Tejada-Simon and Pestka, 1999). Moreover, nutritional studies strengthened these findings showing production of TNF-␣ in individuals following consumption of conventional or probiotic yogurt containing Lactobacillus bulgaricus and Streptococcus thermophilus (Meyer et al, 2007). Interestingly, all tested strains were found effective in influencing iDCs in a mixed lymphocyte reaction with allogeneic T cells, thus suggesting that the phenotype of the inducible immune response is independent of the APC function.…”
Section: Discussionsupporting
confidence: 93%
“…The nutritious and therapeutic benefits of probiotic microorganisms have been most extensively investigated in dairy products such as milk, yogurt, and cheese [21,31,43,66]; however, the potential probiotics properties of LAB isolated from traditional Korean fermentation foods have rarely been reported. In the present study, therefore, to determine the potential uses of LAB as probiotic strains, we assessed LAB isolated from various fermented foods such as dongchimi, kimchi, meju, and soybean paste (doenjang) for their properties including acid resistance, bile tolerance, adhesion to Caco-2 and HT-29 cells, antibiotics resistance, and in vitro antagonism against food-poisoning bacteria.…”
mentioning
confidence: 99%
“…There are many reports about the beneficial effect of the consumption of fermented milk containing the probiotic strain L. casei DN-114001 (de Moreno de LeBlanc, Dogi, et al, 2008;Maldonado Galdeano et al, 2009;Medici, Vinderola, Weill, & Perdigon, 2005;Meyer, Elmadfa, Herbacek, & Micksche, 2007). It was observed that long term administration of fermented milk containing the probiotic bacterium L. casei DN-114001 had immunomodulatory properties and maintained the intestinal homeostasis without adverse secondary effects in mice (de Moreno de LeBlanc, Chaves, et al, 2008).…”
Section: Effect Of Fermented Milk Contained Labmentioning
confidence: 97%